A study on oxygen independent fitness (anaerobic capacity) in pre-collegiate boys of Vijayapur, North Karnataka, India - Siddiq, Mohamed; Dhundasi, Salim A.; Aslam, Mohammed (International Journal of Research in Medical Sciences, 2017)
Background: The anaerobic capacity is a useful concept, its application during exercise testing should considerably increase the information gained regarding cardiovascular function in health and disease. The objective was to evaluate oxygen independent fitness (anaerobic capacity) in pre-collegiate boys (age group of 16-18 years) of Vijayapur, North Karnataka, India. Methods: Eighty seven young adolescent healthy pre-collegiate boys volunteered for this study. The following parameters were recorded: Physical anthropometric parameters: body surface area, body mass index, body fat percentage, Physiological parameters: Blood pressure, physical fitness index test and anaerobic fitness step test. Correlation analysis and Z tests were used to analyze the obtained data. Results: Physical anthropometric parameters of the subjects were found within normal range. Statistically significant exercise induced rise in blood pressure were observed in physical fitness step test. Anaerobic capacity was correlated with body surface area, body mass index, body fat percentage and pre and post exercise blood pressure. Physical fitness index was not correlated with anaerobic capacity. Conclusions:The physical fitness index was in good category, normal physiological response to exercise but physical fitness index not correlated with anaerobic capacity. Anaerobic capacity was found within normal range in pre-collegiate boys of age 16-18 years in study area. Ideal body mass index may not be possible in this age group.